2003
DOI: 10.1117/12.480478
|View full text |Cite
|
Sign up to set email alerts
|

Bi-plane correlation imaging for improved detection of lung nodules

Abstract: Bi-plane correlation imaging (BCI) is a new imaging approach that utilizes angular information from a bi-plane digital acquisition in conjunction with computer assisted detection (CAD) to reduce the degrading influence of anatomical noise in the detection of subtle lesions in planar images. An anthropomorphic chest phantom, supplemented with added nodule phantoms (5-13 mm at the image plane), was imaged from different posterior projections within a ±12 o range by moving the x-ray tube vertically and horizontal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
4
2

Relationship

6
0

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 28 publications
1
26
0
Order By: Relevance
“…7,8 This technique uses the unreconstructed angular projections acquired using an approach similar to tomosynthesis. The projection images are similar to standard mammograms, except that each image is acquired with a lower dose level than that in standard full field digital mammography.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 This technique uses the unreconstructed angular projections acquired using an approach similar to tomosynthesis. The projection images are similar to standard mammograms, except that each image is acquired with a lower dose level than that in standard full field digital mammography.…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary studies have been performed with phantom and human subject data to assess how correlating suspect lesions from multiple views of a standard CAD algorithm may eliminate false positives [14,[20][21][22]. One of those studies of BCI for lung nodule detection demonstrated a FPs false positives sensitivity of 62.5 %, 1.5 false positives per image, and a 0.885 PPV index [14].…”
Section: Discussionmentioning
confidence: 99%
“…One of those studies of BCI for lung nodule detection demonstrated a FPs false positives sensitivity of 62.5 %, 1.5 false positives per image, and a 0.885 PPV index [14]. The BCI reduced sensitivity by 20 % compared to single-view CAD but also reduced false positives by 94 % yielding a 140 % improvement in the PPV [14]. A multiprojection CAD scheme for the chest was used in a study of phantom and human subject data [22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations